1974
DOI: 10.1063/1.1666538
|View full text |Cite
|
Sign up to set email alerts
|

Generalized static electromagnetic fields in relativity

Abstract: A general class of static cylindrically symmetric solutions of the Einstein-Maxwell equations coupled with a zero-rest-mass scalar field is obtained under the assumption -r 2grr = g00gφφgzz. These solutions reduce to Marder's well-known exterior solution in the absence of electromagnetic and scalar fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Here E and B are the absolute values of the electric field strength and magnetic induction, respectively. Selfgravitating static, cylindrically symmetric configurations of such electromagnetic fields have been considered in [62,63,238,272,301] ( in which see also references to earlier work, and more historical details can be found in [294]). In our presentation we follow the lines of [62,63].…”
Section: Electromagnetic Fields In Cylindrical Spacetimesmentioning
confidence: 99%
“…Here E and B are the absolute values of the electric field strength and magnetic induction, respectively. Selfgravitating static, cylindrically symmetric configurations of such electromagnetic fields have been considered in [62,63,238,272,301] ( in which see also references to earlier work, and more historical details can be found in [294]). In our presentation we follow the lines of [62,63].…”
Section: Electromagnetic Fields In Cylindrical Spacetimesmentioning
confidence: 99%
“…This solution (2.27) corresponds to the one obtained in [20] only written in different notation for the constants. Also, using simple relations for hyperbolic functions that are used to write the solution in [22], one can show that our solution corresponds to theirs. Note that in [22], they obtained the solution representing pure magnetic field using the duality between electric and magnetic field.…”
Section: Einstein Maxwell Scalar Fieldmentioning
confidence: 88%
“…Also, using simple relations for hyperbolic functions that are used to write the solution in [22], one can show that our solution corresponds to theirs. Note that in [22], they obtained the solution representing pure magnetic field using the duality between electric and magnetic field. As we will discuss subsequently, our solution has static vacuum solution limit.…”
Section: Einstein Maxwell Scalar Fieldmentioning
confidence: 88%
See 1 more Smart Citation
“…This solution has a long history [3][4][5][6][7][8][9][10], and several authors have reported unexpected features. Thus in [3] it was stated "No solution appears to exist for a line-charge with positive mass", and a similar conclusion appeared in [4,5]. Safko [7] concluded that in this solution there is no charge without mass, and Witten [6] wrote of the intimate connection of mass and charge in the general static cylindrical electromagnetic fields.…”
Section: Introductionmentioning
confidence: 99%